Learning Styles in High School Mathematics - Lira Vázquez, Alejandra; Delfin, Ruth Torres (American Scientific Research Journal for Engineering, Technology, and Sciences, 2017)
In this research, our purpose is to show that when considering the different styles of learning of each student, it is possible to improve the teaching-learning process of High School Mathematics. This research was originated because most of the students in natural way do not have interest in the learning of the Mathematics of High School. In the first place, the exercises were applied to two groups A and B, of 20 students each, considering only their learning styles in the first group. Then the results of their expressed traits of the students of each group are compared, when solving the same exercises of the course of Mathematics II. Finally, it is concluded that when considering the learning styles of the students, positive results are obtained in the teaching-learning process, such as: getting the student to motivate himself in the learning of High School Mathematics and how their evaluation will be better.